2012
DOI: 10.1088/1367-2630/14/5/053044
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate spin density wave versus local magnetic inhomogeneities in Ba(Fe1−xNix)2As2: a57Fe Mössbauer spectral study

Abstract: We report 57 Fe Mössbauer spectral results in pure and doped Ba(Fe 1−x Ni x ) 2 As 2 with x = 0.01 and 0.03. We show that all these materials present a first-order magnetic transition towards a magnetically ordered state. In the doped compounds, a broad distribution of Fe hyperfine fields is present in the magnetic phase. We successfully fit the Mössbauer data in Ba(Fe 1−x Ni x ) 2 As 2 in the framework of two different models: (i) an incommensurate spin density wave (IC-SDW); (ii) a dopant-induced perturbatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…15 However, as we have shown in another paper on 57 Fe Mössbauer spectroscopy in BaFe 2−x Ni x As 2 pnictides, a "two-site model" can satisfactorily fit all spectra below T N . 4 In this "two-site model" a magnetic and a nonmagnetic site are used.…”
mentioning
confidence: 65%
“…15 However, as we have shown in another paper on 57 Fe Mössbauer spectroscopy in BaFe 2−x Ni x As 2 pnictides, a "two-site model" can satisfactorily fit all spectra below T N . 4 In this "two-site model" a magnetic and a nonmagnetic site are used.…”
mentioning
confidence: 65%
“…To compare the effect of Ru substitution (isoelectronic-doping) and Mn substitution (hole- Either C-AFM order or IC-AFM order are predicted by detailed band structure calculations, [305,306] and several local probe measurements such as 75 As nuclear spin resonance [184], 57 Fe Mössbauer [307,308], and muon spin resonance measurements [309] showed that it is probable that it is indeed an IC-AFM structure in Ba(Fe 1−x T M x ) 2 (T M = Co and Ni) compounds.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…NMR measurements [184,308,310] by some groups on underdoped Ba(Fe 1−x Co x ) 2 As 2 (x = 0.02, 0.04) [310] and (x = 0.06) [184] found a strong broadening of the 75 As lines attributable to the appearance of a distribution of internal fields at low temperatures in the magnetically ordered state. A strong anisotropy was also observed, with the broadening more pronounced for H c than for H a b.…”
Section: Methodsmentioning
confidence: 99%
“…The Ce 3+ contribution makes estimation of T N (Fe) from the magnetic data difficult, though we observe a sharp maximum around 80 K in dχT /dT and a broader maximum around 145 K. The overall behavior is consistent with that of the (diamagnetic) La analog β-La 2 O 2 FeSe 2 , which shows non-Curie-Weiss behavior with a broad hump in susceptibility around 91 K which coincides with the loss of magnetic neutron scattering at the Nèel temperature T N . [26], BiFeO 3 [27,28], and AgFeO 2 [29]), iron arsenide superconductors (e.g., doped BaFe 2 As 2 [30,31]), and systems such as Fe x V 3−x S 4 [32], FeP [33], CuFeSe 2 , and CuFeTe 2 [34]. Values of the isomer shift δ and quadrupole splitting E Q , derived by fitting to the paramagnetic spectra (T > 90 K), are presented in Fig.…”
Section: Magnetic Properties Of β-Ce 2 O 2 Fesementioning
confidence: 99%